Mooring tension assessment of a single line kelp farm with quantified biomass, waves, and currents - Fredriksson, David W.; St. Gelais, Adam T.; Dewhurst, Tobias; Coleman, Struan; Brady, Damian C.; Costa-Pierce, Barry Antonio (Frontiers in Marine Science, 2023)
While the number of kelp farms have steadily increased, few have been deployed with sensors to measure mooring tensions with substantial biomass. During the kelp farming season of 2018 - 2019 in Saco Bay, Maine USA, a field study was conducted to assess mooring loads due to environmental conditions and kelp growth. The effort included the deployment of a farm with a 122 m cultivation line and spread mooring with rope, chain, and anchors in 15.2 m of water. The system was deployed with seeded twine in late November and harvested in May. In April, with kelp biomass estimated at 7.8 kg m-1, two load cells were installed to measure mooring tensions in response to currents and waves. The currents and waves were measured with two Acoustic Doppler Current Profilers deployed adjacent to the load cells. From these measurements, we characterized the maximum loading case in response to a complex hydrodynamic environment. The maximum tension occurred on the landward side of the farm even though wave exposure was seaward. The tension in the landward side mooring was dominated by steady drag from the currents going to the east southeast. During this event, the two profilers were positioned on the leading and trailing edges of the farm relative to the prevailing current direction. Velocities measured at 0.5 m bins showed a 26.7% reduction at the depths where the kelp was located. To analyze the dynamic portion of the load cell datasets, the oscillatory components were processed into energy density spectra. Results showed that mooring tensions were not affected by waves at frequencies greater than 0.175 Hz, with most of the energy occurring near 0.12 Hz. The tension spectra did reveal energy at frequencies between 0.0075 and 0.01 Hz, indicating a low frequency response, possibly due to nonuniform velocity profiles inducing vertical motion of the cultivation line. It was also observed that the landward mooring, subjected to higher currents, was more sensitive to oscillating loads than the slack seaward side. The high-fidelity dataset will be useful for numerical modeling validation to further understand these dynamics and to optimize kelp farm designs.